Assessing the Role of Knowledge and Information Sources in the Utilization of Reproductive Health Services Among Adolescents with Disabilities - Atriany Nilam Sari; Dani Ferdian (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2025)
Background: Adolescents with disabilities often face significant barriers in accessing reproductive health services, including physical, social, and informational challenges. Limited knowledge about reproductive health, combined with inadequate or inaccessible information sources, contributes to their vulnerability and underutilization of available services. Many of these adolescents are excluded from comprehensive health education, leading to misconceptions and lack of awareness about their rights and needs. The availability, accuracy, and accessibility of information play a critical role in shaping their understanding and decisions regarding reproductive health. Understanding the role of knowledge and information is essential to promote optimal use of these health services.Objective: This study aims to investigate the correlation between knowledge, information sources, and the utilization of reproductive health services.Method: This study is a quantitative research using a cross-sectional design. It was conducted at Sentra Terpadu Inten Soeweno, Cibinong. A total sampling technique was employed, resulting in 93 adolescent respondents with disabilities. Data analysis was performed using the Chi-square test with a significance level of 0.05. The analysis was conducted using SPSS software version 27Result: The majority of respondents were female adolescents aged 16–19 years with hearing impairments. A significant correlation was found between knowledge and information sources and the utilization of reproductive health services among adolescents with disabilities (p < 0.05)Conclusion: These findings highlight the importance of improving reproductive health education and ensuring accessible information to support informed decision-making and promote equitable health service utilization within this vulnerable population.